Storm clouds rolling in - Dye, Ginny (Dye, Ginny. Bregdan chronicles series, 2015)
"Carrie Cromwell comes of age as the dark clouds of the Civil War swallow the country. Born with a fiery spirit and a strong mind, she finds herself struggling between the common wisdom of the South and the truth she has discovered. The activities of the Underground Railroad and her close friendships with the Cromwell Plantation slaves create difficult choices. But when her decisions put her at odds with her heritage, and challenge her dreams, will she be able to give up all that is precious to her?"--Page 4 of cover.